The Pickle Jar Theory and Effective Time Management: A Philosophical Review - Gunawan, Hery (Technium Social Sciences Journal, 2024)
The purpose of this literature review is to explore effective and efficient time management strategies, utilizing the Pickle Jar Theory as an analogy to illustrate how time influences our thought processes and actions in response to future challenges and changes. This research aims to provide valuable insights into optimizing time management. The study employs a narrative literature review focusing on theoretical frameworks and utilizes secondary data sourced from bestselling books and other relevant time management literature published between 2015 and 2023. The study concludes that time management is a sequential process, where each idea, decision, and action leads to the next. Effective time management is crucial for achieving our goals. The reliance on secondary data introduces potential bias, highlighting the need for future research to incorporate primary data. Subsequent studies should also consider external factors such as individual backgrounds and environments. By gaining a better understanding of time management, individuals are motivated to become punctual and reduce procrastination, thereby enhancing their productivity and efficiency. This research uniquely combines the concept of time management with the Pickle Jar Theory, applying this integrated approach to behavioral contexts to provide novel insights into personal and professional time optimization.